Analysis of the Inception of the Community Enhances its Existence as a Leader Surrounded by a Central Response - Lilis Komariah; Rudianto; Marisi Pakpahan (MultiTech Publisher, 2023)
The rise of women in the era of globalization has brought change; women are no longer merely wives or mothers but have been oriented to the quality of their existence as human beings. With the development of education and career maturity, many women have positions as leaders. There is one key: a woman’s multitasking ability; that is, women have the potential to be a leader outside the home and also a second leader within the household. In the business world, leadership styles have a strong influence on the course of an organization and its survival. The role of leadership is strategic and important in an organization as one of the determinants of its success in achieving its vision, mission, and goals. The leadership theory used in this study is a blend of Situational Leadership Style and Transformational leadership style. Results of the combination of situational-transformational leadership styles by researchers show the accuracy of the application of leadership style in the IWAPI Central Environment in improving its existence as a leader.